Experimental Evaluation of the Driving Parameters in Human–Structure Interaction - Lucà, Francescantonio; Berardengo, Marta; Manzoni, Stefano; Scaccabarozzi, Diego; Vanali, Marcello; Drago, Loris (Vibration, 2022)
Many studies in the literature have already evidenced that pedestrians are able to change the dynamic properties of slender structures (e.g., footbridges and staircases). The aim of this paper is to analyse which pedestrians’ features mostly affect the structure behaviour, in order to properly account for them in a human–structure interaction problem, while disregarding the less relevant ones. This is accomplished by measuring the apparent mass (i.e., the frequency response function between the vibration of the structure at the contact point and the consequent force exerted by the pedestrian to the structure itself) curves of human bodies and coupling them to the dynamics of a slender structure. In more detail, this paper aims at analysing which factors must be accounted for among intra-subject variability (i.e., the dynamic behaviour of the same subject can change because it is characterised by a natural dispersion), inter-subject variability (i.e., different subjects have different dynamic behaviours) and the posture (i.e., the same subject changes posture during motion and this causes a change of his/her dynamic features). The influence of the apparent mass properties on the modal parameters of the hosting structure is addressed by means of a modal approach.